Variation in seed source and seed size influenced the germination and seedling growth of 121Parkia timoriana (Tree bean) in Manipur, India - Loushambam, RS (Indian Journal of Agroforestry, 2023)
Seed origin and its relative mass may have significant impact on performance of the particular tree species. The present study was undertaken with the aim to understand the influence of seed source and seed size variation on germination and seedling growth of Parkia timoriana (DC.) Merr. (Tree bean) an underutilized multipurpose leguminous tree species found in North East India. Seeds were collected from different places of Manipur viz., Ukhrul, Senapati, Tamenglong, Chandel and Churchandpur. The collected seeds were then graded as large (L), medium and small (S) on the basis of length (cm). Irrespective of the seed sources and seed sizes, the seed germination ranges from 88.50 % to 48.50 % and seed of larger size performed better than smaller ones. Among the different seed sources, the seed collected from Ukhrul overweight the other counterparts in all the studied germination and growth parameters. On an average across the different seed sources, there was an increased of 26.11%, 26.09%, 25.34%, 23.54%, 25.93% and 43.63 % of germination percentage, germination capacity, germination energy, peak value, mean germination time and germination value in large size over smaller